The Bangladesh Delta : A Lighthouse Case Study - Pakulski, Ingrid; Laroche, Virginie; Kazi, Swarna; Shawky, Ahmed; Khaleduzzaman, A.T.M.; Urrutia, Ignacio; van Ledden, Mathijs; Browder, Greg; Engle, Nathan (World Bank, Washington, DC, 2021)
This case study report discusses current development strategy for the Bangladesh Delta, which reflects an integrated approach to disaster risk management and water resources management. In this context, special attention is given to the Bangladesh Delta Plan 2100 and the role of the World Bank in Bangladesh’s transition toward sustainable, climate-resilient development. The report goes over key building blocks of the government’s current delta management and highlights some aspects of the Bangladesh Delta Plan 2100 that may also be relevant to other deltas.